A adoção da informação na gestão da aprendizagem organizacional: experiência no Programa de Pós-graduação em Ciência da Informação - Ferreira, Tereza Evâny de Lima Renôr (2011)
Information is configured as focus of relevance in many organizational questions. Information Science, in its ramification, broaches information as a necessary input for the management process. In this specific case, it evidences itself as a constructor element of the organizational learning management. Also, through information, organizational learning is built by intangible actives and it is configured as an essential factor in the development of an institution. Institutes of Higher Education, specially the Post-Graduation programs, face the challenge of working constantly with the sharing, production and dissemination of information. The present research intends to study how information contributes to the organizational management in the area of Information Science. The research also intends to identify, in national and international literature, models of organizational learning. From the models found in the literature, eleven were selected and, among these, two use information in the organizational learning management Dixon s model (1999) and Huber s one (1991). By means of a study and a more detailed analysis, it was possible to note that, from the two models mentioned above, Dixon s (1999) is the one which uses information in the whole process of organizational learning management. In this perspective, the research aims to analyze the use of information in the organizational learning management of the Post- Graduation Program in Information Science of UFPB. Then, informational dimensions were identified as builder elements of organizational learning, functioning as a system of categories to make the comparison. The adopted method is characterized by a case study of quantitativequalitative approach and by exploratory and descriptive characteristics. Interviews and questionnaires were used as research tools. They were based on the elements of the selected model and configured in Likert scale. The data analysis adopted the Content Analysis of Bardin. To examine the adoption of the information in the management of organizational learning, formulated by the model of Dixon (1999), they realized that the twenty-two categories studied, the PPGCI develops sixteen, result that attests to the use of the information in the actions linked to organizational learning in the Program studied.